Proceedings of the 15th International Symposium on Management (INSYMA 2018) 2018
DOI: 10.2991/insyma-18.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

The effect of service Quality to customer satisfaction and loyalty in Sharia Bank

Abstract: Products and prices competition within sharia and conventional banks have an impact on commoditization. To gain market share, sharia banks use halal product as differentiation and service strategy to retain customer through satisfaction to increase loyalty. Customer loyalty expected to increase share from existing customers through up and cross selling, and attract new customers through word of mouth and recommendations. This research aims to analyze the relationship among those variables: service quality with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The existence of good service quality can create confidence in the patients' mind that the services provided are good. These findings support the findings of research conducted by (Agyapong, 2011); (Suseno & Muthohar, 2018), that service quality has a significant effect on patient satisfaction. These findings also support findings from research conducted by (Torres et.…”
Section: Discussionsupporting
confidence: 89%
“…The existence of good service quality can create confidence in the patients' mind that the services provided are good. These findings support the findings of research conducted by (Agyapong, 2011); (Suseno & Muthohar, 2018), that service quality has a significant effect on patient satisfaction. These findings also support findings from research conducted by (Torres et.…”
Section: Discussionsupporting
confidence: 89%
“…Islamic banking and finance have emerged as one of the most impactful aspects that contribute to the economic development of Bangladesh (Suzuki & Uddin, 2016). Several researchers took the initiative of studying issues about the service quality of Islamic banks in Bangladesh (Suseno & Muthohar, 2018;Mahmood & Osman, 2015;Shampa & Hasan, 2015;Rashid et al, 2009). A study was undertaken by Mahmood and Osman (2015) to understand customers' perception of Islamic banks in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, the area of Islamic banking has become one of the fastest-growing sectors in different regions across the globe (Dandis & Wright, 2020;Amirzadeh & Shoorvarzy, 2013). Despite being a relatively new occurrence compared to conventional banking; Islamic banking has been widely accepted by Muslim alongside with non-Muslim consumers at large (Suseno & Muthohar, 2018;Amat et al, 2014). Thus, Islamic banking has experienced expansion not only in Muslim countries but in many Western countries as well (Rehman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tabligh is related to customer services quality in sharia bank (Ab Hamid et al, 2021, p. 5) that found by researches affecting to customer satisfaction that in turn would affect to their retention to sharia bank. Suseno & Muthohar, (2018) examine the relationship between service quality, customer satisfaction, and customer loyalty and found that customer satisfaction influenced by service quality el Barka: Journal of Islamic Economics and Business while loyalty influenced both by service quality and costomer satisfaction. In the same line, Rusmahafi & Wulandari, (2020) investigated the relationship between brand image, service quality, and customer value on customer satisfaction.…”
Section: Methodsmentioning
confidence: 99%